The Gut–Brain Axis and Its Relation to Parkinson’s Disease: A Review - Klann, Emily M.; Dissanayake, Upuli; Gurrala, Anjela; Farrer, Matthew; Shukla, Aparna Wagle; Ramirez-Zamora, Adolfo; Mai, Volker; Vedam-Mai, Vinata (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease is a chronic neurodegenerative disease characterized by the accumulation of misfolded alpha-synuclein protein (Lewy bodies) in dopaminergic neurons of the substantia nigra, which contribute to the development of both motor (bradykinesia, tremors, stiffness, abnormal gait) and non-motor symptoms (gastrointestinal issues, urinogenital complications, olfaction dysfunction, cognitive impairment). Despite tremendous progress in the field, the exact pathways and mechanisms responsible for the initiation and progression of this disease remain unclear. However, recent research suggests a potential relationship between the commensal gut bacteria and the brain capable of influencing neurodevelopment, brain function, and health. This bidirectional communication is often referred to as the microbiome-gut-brain axis. Accumulating evidence suggests that the onset of non-motor symptoms, such as gastrointestinal manifestations, often precede the onset of motor symptoms and disease diagnosis, lending support to the potential role that the microbiome-gut-brain axis might play in the underlying pathological mechanisms of Parkinson’s disease. This review will provide an overview of and critically discuss the current knowledge of the relationship between the gut microbiota and Parkinson’s disease, the role of α-synuclein in non-motor disease pathology, proposed pathways constituting the connection between the gut microbiome and the brain, existing evidence related to pre- and probiotic interventions, and will highlight the potential opportunity for the development of novel preventative measures and therapeutic options that could target the microbiome-gut-brain axis in the context of Parkinson’s disease.